Numerical Study of the Wide‐angle Polarization‐Independent Ultra‐Broadband Efficient Selective Solar Absorber in the Entire Solar Spectrum. Issue 7 (16th June 2017) - Wu, Dong; Liu, Yumin; Xu, Zenghui; Yu, Zhongyuan; Yu, Li; Chen, Lei; Liu, Chang; Li, Ruifang; Ma, Rui; Zhang, Jinqiannan; Ye, Han
Abstract : Increasing the absorption efficiency of solar radiation has great significance for the renewable energy applications, such as residential water heating, seawater desalination, wastewater treatment and solar thermophotovoltaic devices. Optical absorbers based on metamaterials have been widely investigated using a variety of structural designs. However, the near‐ideal solar thermal absorber has not yet been demonstrated, which has a near unity absorption from the ultraviolet to the near‐infrared region and meanwhile an absorption close to zero in the mid‐infrared region. Here, using FEM and FDTD methods respectively, we propose and numerically demonstrate an ultra‐broadband selective solar absorber with an extremely high absorption efficiency above 99% within the range of 435–1520 nm. And meanwhile the emissivity of the nanostructure is below 20% in mid‐infrared region. The total photothermal conversion efficiency of the proposed solar absorber can reach 91.53%, which is very close to the photothermal conversion efficiency (95.6%) of the ideal cut‐off absorber. The physical mechanisms of the nearly perfect absorption are also investigated and analyzed clearly, which is attributed to the hybridization of localized surface plasmon resonance, gap plasmon resonance, and propagating surface plasmon resonance. Particularly, the near‐ideal efficient selective absorption can still be maintained very well at a wide incident angle regardless of the incident light polarization. Owing to the characteristics such as polarization and angle independence, broadband operation, near‐perfect absorption and strong spectral selectivity, the solar absorbers are promising candidates for solar energy harvesting, stealth technology, and thermo‐photovoltaic energy conversion. Abstract : The efficient selective solar absorber has an extremely high absorption above 99% at the range of 435–1520 nm and a low emission below 20% at the range beyond 2500 nm, which is in good agreement with the spectral selectivity of ideal solar absorber. The solar absorbers are promising candidates for solar energy harvesting, stealth technology, and thermo‐photovoltaic energy conversion.